Circulating calprotectin as a biomarker of laryngeal carcinoma - BİNNETOĞLU, ADEM; YUMUŞAKHUYLU, ALİ CEMAL (SPRINGER, 2017)
Calprotectin is an S100 protein and marker of inflammation found in neutrophils and monocytes; S100 proteins are a family of calcium-modulated proteins. The aim of this study was to determine if the serum concentration of calprotectin is higher in patients with laryngeal carcinoma than in patients with benign laryngeal pathologies and controls. The study included 107 participants. The serum calprotectin concentration was analyzed using the calprotectin ELISA (enzyme-linked immunosorbent assay) kit (Calpo AS, Norway). EDTA-serum for analysis was collected prior to surgery from patients with laryngeal carcinoma (n = 41), those with a benign laryngeal pathology (Reinke's edema, vocal nodules, etc.) (n = 32), and healthy controls (n = 34). The median serum calprotectin concentration was significantly higher in the laryngeal carcinoma group (2179.6 mu g L-1) than in the benign laryngeal pathology group (727.84 mu g L-1) and control group (733.73 mu g L-1) (P < 0.05). The median serum calprotectin concentration in patients with advanced-stage laryngeal cancer (5854.,4 mu g L-1) was significantly higher than in those with early-stage laryngeal cancer (971.84 mu g L-1) (P < 0.05); however, there was not a significant difference in the median calprotectin concentration between the control and benign laryngeal pathology groups (P > 0.05). Furthermore, the median serum calprotectin concentration in the patients with early-stage laryngeal cancer (n = 21) (971.84 mu g L-1) was significantly higher than that in the benign laryngeal pathology and control groups (n = 64) (730.6 mu g L-1) (P < 0.05). The serum calprotectin concentration was strongly correlated with poor survival and advanced-stage laryngeal carcinoma. Malignant laryngeal cancer patients (n = 4) that died during follow-up had a higher median serum calprotectin concentration (9468.4 mu g L-1) than those that remained alive (n = 37) (857.78 mu g L-1) (P < 0.05). The serum calprotectin concentration is higher in patients with laryngeal carcinoma than in those with benign laryngeal pathologies and healthy controls. The present findings show that the serum calprotectin concentration might be used as a marker to discriminate between laryngeal carcinoma and benign laryngeal pathologies. Additional research is needed to further assess the value of this parameter as a useful tumor marker for the diagnosis, treatment, and follow-up of laryngeal carcinoma.
Keywords: Calprotectin; Biomarker; Laryngeal carcinoma; SQUAMOUS-CELL CARCINOMA; INFLAMMATION; EXPRESSION; CANCER; S100A9; SERUM